1999
DOI: 10.1021/jm980250e
|View full text |Cite
|
Sign up to set email alerts
|

Design and Synthesis of a Potent Cyclic Analogue of the Myelin Basic Protein Epitope MBP72-85:  Importance of the Ala81Carboxyl Group and of a Cyclic Conformation for Induction of Experimental Allergic Encephalomyelitis

Abstract: Experimental allergic encephalomyelitis (EAE) is induced in susceptible animals by immunodominant determinants of myelin basic protein (MBP), such as guinea pig sequence MBP72-85. Two linear and one cyclic analogues based on MBP72-85 have been synthesized and evaluated for EAE induction in Lewis rats. The linear peptide Gln1-Lys2-Ser3-Gln4-Arg5-Ser6-Gln7-+ ++Asp8-Glu9-Asn10-Pro11-Val12 (1) was found to induce EAE, while substitution of the Asp residue at position 8 with Ala resulted in an analogue (2) which su… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
68
0
8

Year Published

1999
1999
2011
2011

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 55 publications
(76 citation statements)
references
References 41 publications
(115 reference statements)
0
68
0
8
Order By: Relevance
“…15,20,[23][24][25][26][27][28] We had previously demonstrated that injection of Lewis rats with linear or cyclic guinea pig MBP 72-85 peptides induced EAE. 19 15 In our in vivo rat studies, EAE was induced by the agonist guinea pig epitope MBP [72][73][74][75][76][77][78][79][80][81][82][83][84][85] and not by the human MBP 83-99 agonist peptide. Injections with human agonist peptides caused anaphylactic shock and weak signs of EAE.…”
Section: Discussionmentioning
confidence: 99%
“…15,20,[23][24][25][26][27][28] We had previously demonstrated that injection of Lewis rats with linear or cyclic guinea pig MBP 72-85 peptides induced EAE. 19 15 In our in vivo rat studies, EAE was induced by the agonist guinea pig epitope MBP [72][73][74][75][76][77][78][79][80][81][82][83][84][85] and not by the human MBP 83-99 agonist peptide. Injections with human agonist peptides caused anaphylactic shock and weak signs of EAE.…”
Section: Discussionmentioning
confidence: 99%
“…Effort must be made to understand: (a) the forces that determine the folding of the epitope; (b) the conservation of the linearity and extended structure of the altered epitope; (c) the molecular features of the altered epitope that maximize the productive interactions with HLA-DR2 and minimize the contacts with TCR. The linear peptides were prepared on 2-chlorotrityl chloride resin (CLTR-Cl) using the Fmoc/tBu solid-phase methodology [28][29][30][31]. The first N a Fmoc (9-fluorenylmethyloxycarboxyl)-protected amino acid (Fmoc-Pro-OH) was esterified to the resin in the presence of diisopropylethylamine (DIPEA) in dichloromethane (DCM) in 1 h at RT [28][29][30][31].…”
Section: Resultsmentioning
confidence: 99%
“…The linear peptides were prepared on 2-chlorotrityl chloride resin (CLTR-Cl) using the Fmoc/tBu solid-phase methodology [28][29][30][31]. The first N a Fmoc (9-fluorenylmethyloxycarboxyl)-protected amino acid (Fmoc-Pro-OH) was esterified to the resin in the presence of diisopropylethylamine (DIPEA) in dichloromethane (DCM) in 1 h at RT [28][29][30][31]. DCM/MeOH/DIPEA (85:10:5) was then added and the resulting mixture was stirred for another 10 min at RT.…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations